Trauma Healing pada Penderita Depresi di Nganjuk - Wajdi, Muh Barid Nizarudin (LP3M STAI Darussalam Krempyang Nganjuk, 2019)
Mental disorders due to depression in the Nganjuk regency which consists of 20 sub-districts were signaled to increase. This is the subject of discussion and will be a special consideration for sufferers' families and can affect the quality of life of patients, families, and the surrounding community. this research uses a hoslistic approach. held in each district 7 to 15 people to attend the socialization meeting. The total number of participants in 20 districts and centered in several zones was 140 people. the results showed that pasung was performed because the patient had dropped out of medication; not opinion of access to treatment; no money for treatment; a place to stay far from the health care center; medicine not available; disturbing people around him; family feels disturbed; endanger yourself and others / environmental safety; family does not know what to do, lack of knowledge; family shame; handling carried out from generation to generation in the area; as a treatment and is a punishment. this is because there are no local regulations regarding the handling of psychotic bums and mental disorders.